The expression \((5x + 3)^2\) can be expanded using the formula \((a + b)^2 = a^2 + 2ab + b^2\), where \(a = 5x\) and \(b = 3\).
Substitute \(a = 5x\) and \(b = 3\) into the formula: \[ (5x + 3)^2 = (5x)^2 + 2 \cdot (5x) \cdot 3 + 3^2 \]
Calculate each term separately: \[ (5x)^2 = 25x^2 \] \[ 2 \cdot (5x) \cdot 3 = 30x \] \[ 3^2 = 9 \]
Combine the simplified terms: \[ 25x^2 + 30x + 9 \]
\(\boxed{25x^2 + 30x + 9}\)
Oops, Image-based questions are not yet availableUse Solvely.ai for full features.
Failed. You've reached the daily limit for free usage.Please come back tomorrow or visit Solvely.ai for additional homework help.